2015
DOI: 10.1111/ijpo.12005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced retinal nerve fibre layer thickness in children with severe obesity

Abstract: These findings suggest that adiposity and obesity-related inflammatory factors may be associated with the loss of retinal ganglion cells in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
1
31
2
Order By: Relevance
“…Obesity and MetS associated with chronic inflammation can affect most systems in the body (1,2,20). This chronic inflammation also has the potential to produce changes in the retina and macular layer (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and MetS associated with chronic inflammation can affect most systems in the body (1,2,20). This chronic inflammation also has the potential to produce changes in the retina and macular layer (20).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and MetS associated with chronic inflammation can affect most systems in the body (1,2,20). This chronic inflammation also has the potential to produce changes in the retina and macular layer (20). Indeed, previous MetS: metabolic syndrome studies have shown that obesity reduces the thickness of the retinal nerve fiber layer in children and affects choroid tissue (21,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The RNFL and the thickness of choroid tissue can be affected by obesity. Previous studies have shown that obesity causes a thinning in RNFL thickness in children (23,24). Low level systemic inflammation is known to occur in obesity (25)(26)(27).…”
Section: Discussionmentioning
confidence: 97%
“…The recent reports demonstrated that the central corneal thickness and intraocular pressure were increased while as mean thickness of RNFL and retinal ganglion cell and choroidal thickness (CT) were decreased in the morbidly obese subjects [17][18][19]. However, another study has reported that CT increased in obese children [20].…”
Section: Editorialmentioning
confidence: 99%